Meningkatkan Hasil Belajar Ilmu Pendidikan Sosial Menggunakan Pembelajaran Kontekstual pada Siswa Kelas VII SMPN 11 Bandar Lampung - Robiah, Siti (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The method used in this research is Classroom Action Research or classroom action research which is carried out in 3 cycles. The research was conducted in October 2019. This study aims to determine the increase in student learning activities and learning outcomes during learning by applying contextual learning to social studies subjects in class VII SMP Negeri 11 Bandar Lampung TP. 2019/2020. The results of the research and observations were obtained: 1) student learning outcomes measured from the cognitive aspect, namely the class average in cycle I was 69.29 with classical completeness 65.71 and 2) in cycle 2 the class average value was 76.86 with completeness classical reached 80%, followed by 3) in the third cycle the average value was 81.57 with 91.43% classical completeness. Based on the results of the study, it can be concluded that the application of contextual learning can improve learning outcomes in the implementation of social studies learning in class VI SMP Negeri 11 Bandar Lampung TP 2019/2020.